Differential Functions of Two Metalloproteases, Mrmep1 and Mrmep2, in Growth, Sporulation, Cell Wall Integrity, and Virulence in the Filamentous Fungus Metarhizium robertsii - Zhou, Rong; Zhou, Xiazhi; Fan, Ali; Wang, Zhangxun; Huang, Bo (Frontiers in Microbiology, 2018)
The Metarhizium genus of filamentous entomopathogenic fungi plays a pivotal role in regulating insect populations. Metalloproteases (MEPs) are a widely distributed and diverse family of hydrolytic enzymes that are important toxicity factors in the interactions between fungi and their hosts. Herein, we characterized two MEPs, Mrmep1 and Mrmep2, in Metarhizium robertsii using gene deletion. Growth rates of the resulting ΔMrmep1 and ΔMrmep2 mutants decreased by 16.2 and 16.5%, respectively, relative to the wild-type (WT) strain. Both mutants were less sensitive to cell wall-perturbing agents, sodium dodecyl sulfate and Congo red than the WT strain, whereas did not show any obvious changes in fungal sensitivity to ultraviolet B irradiation or heat stress. The conidial yield of ΔMrmep1, ΔMrmep2, and ΔMrmep1ΔMrmep2 mutants decreased by 56.0, 23, and 53%, respectively. Insect bioassay revealed that median lethal time values against Galleria mellonella increased by 25.5% (ΔMrmep1), 19% (ΔMrmep2), and 28.8% (ΔMrmep1ΔMrmep2) compared with the WT strain at a concentration of 1 × 107 conidia mL-1, suggesting attenuated fungal virulence in the ΔMrmep1, ΔMrmep2, and ΔMrmep1ΔMrmep2 strains. During fungal infection, transcription levels of Mrmep1 was 1.6-fold higher than Mrmep2 at 36 h post inoculation. Additionally, transcription levels of gallerimycin gene were 1.2-fold, 2.18-fold, and 2.5-fold higher in insects infected with the ΔMrmep1, ΔMrmep2, or ΔMrmep1ΔMrmep2 mutant than those infected with the WT strain, respectively. Our findings suggest that Mrmep1 and Mrmep2 are differentially contributed to the growth, sporulation, cell wall integrity, and virulence of M. robertsii.